Identificación del pie de riesgo a los pacientes diabéticos que reciben terapia renal sustitutiva de la unidad de diálisis del Hospital Teófilo Dávila. Machala 2014. - Palma Sánchez, Ronald Manuel (2015)
Diabetes Mellitus is a metabolic disease that affects different organs and is currently in the ascendancy, as their most frequent complications among this nephropathy, retinopathy and diabetic neuropathy. Diabetes is the third leading cause of advanced renal failure. The average time since diagnosis of diabetes mellitus to the stage of terminal renal failure is 20-30 years for diabetic neuropathy can be present even in the diagnosis of Diabetes Mellitus, so the development of ulcers is higher in this group of patients. It is important to identify the degree of risk for developing ulcers in the foot, while we prevent complications such as diabetic foot, avoiding a better way amputation of the lower limbs.